Tannic acid-based nanopesticides coating with highly improved foliage adhesion to enhance foliar retention. Issue 46 (28th August 2019) - Yu, Manli; Sun, Changjiao; Xue, Yumiao; Liu, Chang; Qiu, Dewen; Cui, Bo; Zhang, Yan; Cui, Haixin; Zeng, Zhanghua
Abstract : Poor utilization of conventional pesticides has resulted in overuse, which increases cost, toxicity to other non-target organisms, concerns about human health and safety, groundwater and contamination, with ecosystem destruction and food pollution. Abstract : Poor utilization efficiency of conventional pesticide formulation has resulted in overuse, which could increase costs, toxicity to other non-target organisms, concerns about human health and safety, groundwater contamination, causing ecosystem destruction and food pollution. The folia-adhesive formulation is supposed to enhance foliar retention time and utilization efficiency. According to the microstructure of the foliage, the nanopesticides surfaces were modified by affinity groups to improve folia adhesion and decrease the loss from crop foliage. In this study, tannic acid, a bioadhesive natural molecule, has been applied to develop abamectin nanopesticide (Abam-PLA-Tannin-NS) and azoxystrobin nanopesticide (Azox-PLA-Tannin-NS) with strong adhesion to foliage by chemical modification. Abam-PLA-Tannin-NS and Azox-PLA-Tannin-NS presented better photostability and continuous release behavior. The retention rates of Abam-PLA-Tannin-NS and Azox-PLA-Tannin-NS on the foliage was remarkably enhanced by more than 50%, compared with unmodified nanopesticides. Resultantly, the indoor toxicity of Abam-PLA-Tannin-NS and antifungal activity of Azox-PLA-Tannin-NS were enhanced. The interaction force between tannic acid coating nanoparticles and foliage was mainly from hydrogen bonding. Our findings could be beneficial to develop novel leaf-adhesive nanopesticides with high retention time and bioavailability.